1980
DOI: 10.1172/jci109694
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphology and Neuropharmacology of the Human Penis

Abstract: A B S T R A C T The neuromorphology and neuropharmacology of the human penis are only briefly described in literature. The present study was undertaken to define the adrenergic and cholinergic neuromorphology of the human corpus cavemosum (CC) and corpus spongiosum and to evaluate the in vitro response of the CC to pharmacologic stimulation. Human penile tissue was obtained from six transsexual patients undergoing penectomy. For morphologic study, the tissue was processed for (a) hematoxylin and eosin staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(22 citation statements)
references
References 25 publications
3
18
1
Order By: Relevance
“…The present finding that ATP relaxes the corporal cavernosal tissue is con sistent with the theory that ATP (or another purine nucleotide) is a NANC transmitter in the corpora cavernosa. Additional evidence suggesting the possible role of purinergic nerves in cavernosal tissue came from the electron microscopic study of human erectile tissue by Benson et al [7] who found neural varicosities with large opaque vesicles which fit the descriptions for purinergic or peptider gic nerve fibers. These 800-to 2.000-Â opa que vesicles were seen frequently in their ma terial and are similar, though not specific, to those which Burnstock [ 12] has proposed to contain ATP as a neurotransmitter.…”
Section: Discussionmentioning
confidence: 92%
“…The present finding that ATP relaxes the corporal cavernosal tissue is con sistent with the theory that ATP (or another purine nucleotide) is a NANC transmitter in the corpora cavernosa. Additional evidence suggesting the possible role of purinergic nerves in cavernosal tissue came from the electron microscopic study of human erectile tissue by Benson et al [7] who found neural varicosities with large opaque vesicles which fit the descriptions for purinergic or peptider gic nerve fibers. These 800-to 2.000-Â opa que vesicles were seen frequently in their ma terial and are similar, though not specific, to those which Burnstock [ 12] has proposed to contain ATP as a neurotransmitter.…”
Section: Discussionmentioning
confidence: 92%
“…The primary site of the occlusion has been postulated to be within the subtunical venules, which are the small corporal veins under the tunical wall. The fundamental mechanics of occlusion had been presumed to be the compressive forces exerted by the expanding corpora against the less compliant tunica, essentially 'squashing' the subtunical venules (Benson et al 1980;Anderson et al 1984;Fournier et al 1987;Lue & Tanagho 1987;Breza et al 1989;Chaudhoke & Lue 1989;Aboseif et al 1990;Banya et al 1990). Certain phenomena have not been completely explained by this mechanism, such as: (i) actual occlusion is not total, and (ii) it appears that the tunica may not be taut (i.e.…”
Section: Veno-occlusive Function Of the Corpora Cavernosamentioning
confidence: 99%
“…Over a century ago, Anrep and Cybulsky [3] re ported that erection is atropine-resistant and Nikolsky [22] found that erection induced by stimulation of the nervi erigentes could be abolished by atropine. Neverthe less, the question of the atropine-sensitivity of erection remains, with in vivo studies yielding results that are both contradictory [5,7,14,27] and confirmatory [9,24], 1 Dr. Stief was sponsored by a grant from the Deutsche For schungsgemeinschaft.In vitro findings have also been conflicting: no effect [4,8]; relaxation [6,13] The aim of this study was to elucidate the role of ACh in canine penile erection in vivo. …”
mentioning
confidence: 99%